Simon Firkovič and his role in preserving the Karaim language - Kobeckaitė, Halina (Vilnius University Proceedings, 2024)
Lithuania is a unique place in the world where the Karaim language is still alive. Living in Lithuania for 625 years, Karaims have spoken their mother tongue at home and in their families, also used their language in religious service, and learned it at school. The Senior priest of Trakai community Simon Firkovič (1897–1982) played an important role in fostering and preserving his native Karaim. He was elected to that position in 1922 and served there for 60 years. The article looks into his activities in two strands: him working for the community in his religious and teaching duties as well as being a poet and writer, in a more individual vein following his vocation to cultivate, safeguard, facilitate, and nurture Karaim identity.